2017
DOI: 10.1111/eip.12506
|View full text |Cite
|
Sign up to set email alerts
|

Brief interactive psychoeducation for caregivers of patients with early phase psychosis in Yogyakarta, Indonesia

Abstract: This study demonstrated that brief psychoeducation with caregivers of patients with early phase psychosis was feasible in our setting, significantly improved caregivers' knowledge, and resulted in improved regularity of contact with health providers and compliance with pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…A total of 100 patients with early psychosis and their caregivers were recruited as part of an intervention study (Marchira, 2012 ). The inclusion criteria were that patients should: (1) be suffering the first episode of any psychotic disorder, with diagnosis established by at least two psychiatrists according to International Statistical Classification of Diseases and Related Health Problems-10th Revision (ICD-10) criteria, (2) be aged 15–30 years old, with caregiver's aged 18–70 years old, (3) have given informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 100 patients with early psychosis and their caregivers were recruited as part of an intervention study (Marchira, 2012 ). The inclusion criteria were that patients should: (1) be suffering the first episode of any psychotic disorder, with diagnosis established by at least two psychiatrists according to International Statistical Classification of Diseases and Related Health Problems-10th Revision (ICD-10) criteria, (2) be aged 15–30 years old, with caregiver's aged 18–70 years old, (3) have given informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The data for the analyses reported here were collected from October 2010 to March 2012 during in-depth interviews with caregivers. Data from these interviews were analyzed and coded to allow quantitative analysis (Marchira, 2012 ). The protocol of this study was approved by the Ethical Committee of the Faculty of Medicine Gadjah Mada University, Jogjakarta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This number varied widely depending on whether the family residence was urban (27%), semi-urban (41%), or rural (55%); it also varied by education level of caregiver. In a more recent first-episode study (that included a psychoeducation intervention), Marchira et al (2019) reported that 60% of caregivers expressed medical explanatory models (after entering treatment), and 64% indicated they had sought care from a nonmedical healer prior to contact with a psychiatrist.…”
Section: Survey Datamentioning
confidence: 99%
“…RAMI ET AL., 2018;MARCHIRA ET AL., 2018;MARCHIRA ET AL.,2019). Todos abordaram pacientes considerados crônicos, não se limitando aos no primeiro episódio de psicoses.…”
unclassified